Pembelian Impulsif dalam Live Streaming TikTok Shop: Peran Keterikatan Endorsement dan Perbedaan Gender sebagai Pemoderasi - Guruh Ghifar Zalzalah; Oktavia Nurul Khasanah; Fikri Farhan (Jurnal Maksipreneur, 2026)
This study aims to determine the relationship between consumer attachment to endorsements and impulse purchases, moderated by gender, by adopting the Elaboration Likelihood Model (ELM) and Attachment Theory. This research is a quantitative study using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.1.1.1. Data collection used a questionnaire and non-probability sampling, specifically purposive sampling, targeting TikTok users in Indonesia who have made more than one purchase via live streaming, for a total of 300 respondents. The results showed that the suitability of influencer live streaming content affects consumer attachment to live streaming and influencers; consumer attachment to live streaming and influencers affects attachment to endorsements; and attachment to endorsements affects impulse purchases. However, gender does not significantly moderate the relationship between consumer attachment to endorsements and impulse purchases.